An example of conflicts of interest as pandering disincentives - Chiba, Saori (2015)
Consider an uninformed decision maker (DM) who communicates with a partially informed agent through cheap talk. DM can choose a project to implement or the outside option of no project. Unlike the current literature, we show that if there exists multiple dimensions of conflicts of interests between a single agent and a single receiver (DM), an increase in the conflict of interest in one dimension may actually improve cheap talk communication given that it acts as a countervailing force to conflicts of interest in other dimensions.